HUBUNGAN PENGETAHUAN IBU DAN DUKUNGAN SUAMI DENGAN MOTIVASI IBU DALAM MEMBERIKAN ASI EKSLUSIF PADA BAYI DI PUSKESMAS BENTENG KOTA AMBON - Melawati Wakano; Petriana E. Mahmud; Ivonny Torimtubun (Poltekkes Kemenkes Malang, 2021)
The high rate of infant mortality in Indonesia is partly due to the low level of exclusive breastfeeding during the first 6 months of a baby life. The purpose of this study was to analyze the relationship between knowledge and support from husbands and mother motivation in breastfeeding babies. This type of research is analytic survey with a cross sectional study. because in this study the independent and dependent variables will be observed at the same time, so there is no follow up in this research. Sampling technique Total sampling with 71 respondents. The research data were obtained by giving a questionnaire to see the knowledge of mothers and husband support with the mother motivation in giving exclusive breastfeeding. Data analysis used Chi Square statistical test. The results showed that there was a relationship between mother knowledge and mother motivation in giving exclusive breastfeeding with a value of P equal 0,000, while husband support and motivation for exclusive breastfeeding were found to have a relationship with a value of P equal 0,000, therefore the motivation of mothers in exclusive breastfeeding is highly supported by mother knowledge and support from her husband.